Autologous blood transfusion: Literature review - Paredes Aspilcueta, Miguel Giovanni (2024)
Introduction: Autologous blood transfusion, also known as autotransfusion, allows a patient to receive their own previously collected and stored blood, reducing the risks associated with homologous transfusion. Objective: To analyze and describe the modalities of autologous transfusion, its benefits, indications, limitations, and risks in different clinical scenarios. Methods: A narrative review of studies published between 2015 and 2025 was conducted using biomedical databases such as PubMed, Cochrane, and the Pan American Health Organization (PAHO). A total of 43 references were included, encompassing systematic reviews, clinical trials, and observational studies. The methodological quality of the studies was assessed, and information was synthesized according to each autologous transfusion modality: preoperative blood deposit, acute normovolemic hemodilution, and intraoperative blood salvage. Results: Autologous transfusion was found to reduce the need for homologous blood transfusion, minimize the risk of immunological reactions, and enhance transfusion safety. Preoperative blood deposit is useful in elective surgeries with a high risk of bleeding, acute normovolemic hemodilution in procedures with moderate blood loss, and intraoperative blood salvage in massive hemorrhages. However, limitations include high costs, the need for specialized infrastructure, and restrictions in patients with severe anemia. Conclusion: Autologous transfusion is a key strategy in transfusion medicine. Its implementation depends on hospital infrastructure and planning. The integration of Patient Blood Management (PBM) strategies and standardized protocols will optimize its clinical application.